2013
DOI: 10.1590/s0036-46652013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Envenoming by coral snakes (Micrurus) in Argentina, during the period between 1979-2003

Abstract: SUMMARYEnvenomation by coral snakes (Micrurus sp.) is one of the most dangerous injuries in America and it is considered as a serious medical emergency, however bites by these snakes appear to be rare. We analyzed epidemiological data, clinical signs and antivenom use in Argentina during the period between . During this period of study 46 non-fatal Micrurus bites were reported. The majority of cases were men from 31 to 40 years old. Bites occurred primarily in spring and summer. Most cases were reported from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…This elevated incidence may be the result of the lack of protective equipment, especially in regions where there is no use of machinery in agricultural activities 14 . In many studies undertaken in Brazil 26 , 46 , and in the world 47 - 49 , it was reported that above all snakebites affected the extremities of the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…This elevated incidence may be the result of the lack of protective equipment, especially in regions where there is no use of machinery in agricultural activities 14 . In many studies undertaken in Brazil 26 , 46 , and in the world 47 - 49 , it was reported that above all snakebites affected the extremities of the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Coral snakes ( Elapidae ) comprise some 71 species that are widely distributed in tropical and subtropical regions of the New World, from Southeastern USA to Central Argentina [ 1 , 2 , 3 ]. Envenomings by these snakes are far less frequent than those inflicted by viperids, but are of medical concern [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Las manifestaciones locales suelen ser muy leves, observándose una o dos punturas, o incluso ninguna, refiriéndose dolor local de intensidad variable, con progresión proximal (2,9,11) . Los elementos neurológicos locales como parestesias se presentan en menos de la mitad de los casos (2,9,11,12) . En este caso se evidenció una única puntura, dolor y edema leve sin equi-mosis, ni hemorragias o manifestaciones neurológicas locales.…”
Section: Discussionunclassified